2020
DOI: 10.1039/c9cp06620a
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of interaction-induced nonlinear optical properties of molecular complexes. II. Halogen-bonded systems

Abstract: Interaction-induced electronic and vibrational (hyper)polarizabilities of halogen-bonded complexes were decomposed into different interaction types (electrostatic, exchange, induction and dispersion).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…In addition to participating in hydrogen-bonding interactions, the heavier halides (Cl, Br, and I) are also known to form halogen bonds (XB): attractive interactions between the electrophilic region, or σ-hole, of a halogen atom and a nucleophile . Nitrogen is a common XB acceptor, and a few computational studies have reported linear, halogen-bonded configurations of the form HCN···XH for X = Br and I. Studies of the HCN/HX heterogeneous dimer focus exclusively on either the HB or the XB configurations, and to date no studies have looked more broadly at both possiblilities for these systems. Both halogen and hydrogen bonds are important to many fields, such as supramolecular chemistry and biochemistry, and extensive research has been done to investigate the relationship between these two noncovalent interactions. Taking a look at how they compete in a relatively simple dimer system that is both computationally and experimentally accessible can give researchers insight into their roles in more complex systems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to participating in hydrogen-bonding interactions, the heavier halides (Cl, Br, and I) are also known to form halogen bonds (XB): attractive interactions between the electrophilic region, or σ-hole, of a halogen atom and a nucleophile . Nitrogen is a common XB acceptor, and a few computational studies have reported linear, halogen-bonded configurations of the form HCN···XH for X = Br and I. Studies of the HCN/HX heterogeneous dimer focus exclusively on either the HB or the XB configurations, and to date no studies have looked more broadly at both possiblilities for these systems. Both halogen and hydrogen bonds are important to many fields, such as supramolecular chemistry and biochemistry, and extensive research has been done to investigate the relationship between these two noncovalent interactions. Taking a look at how they compete in a relatively simple dimer system that is both computationally and experimentally accessible can give researchers insight into their roles in more complex systems.…”
Section: Introductionmentioning
confidence: 99%
“…Interaction induced properties of Watson-Crick amino acid pairs have also been studied with higher orders of SAPT 68 and also with taking into account nuclear relaxation effects for small hydrogenand halogen-bonded dimers in the order up to interaction first hyperpolarizabilities. 69,70 The SAPT0 mean absolute errors for the interaction energy, dipole moment, and polarizability are, respectively, 0.50 kcal mol −1 , 0.039 D, and 0.15 Å 3 . Hence, SAPT0 is in qualitative agreement with the coupled cluster reference.…”
Section: B Sapt0 Decomposition Of the Interaction-induced Properties ...mentioning
confidence: 98%
“…The addition of two fluorine atoms to the aromatic backbone, 24DF, increases the σ-hole potential but does not add any competing XB acceptors. Consequently, the main XB is an I••• OC; 2.891(2) Å and 173.51 (11)°.…”
mentioning
confidence: 98%
“…σ-Hole interactions, resulting from an attraction between an electron-deficient σ-hole on a halogen atom, and an electron-rich region on a Lewis base, can offer high directionality and tunability, which make them well-suited for the directed assembly of desired and robust supramolecular architectures . These properties have provided a foundation for halogen-bond-based structural chemistry with applications in a wide range of fields, fromcatalysis, , luminescence, nonlinear optics, , energetics, gels, and polymers, to molecular recognition, self-assembly, , and drug discovery . The strength of the halogen bond is directly related to the magnitude of the σ-hole, for which molecular electrostatic potentials are frequently used as a yardstick. , Stronger halogen bonds lead to synthon robustness, which means that we need access to an extensive library of molecules possessing large σ-hole potentials in order to impart supramolecular synthetic reliability.…”
mentioning
confidence: 99%